Transformasi Peran Guru Di Era Digital: Meningkatkan Efektivitas Manajemen dan Administrasi Madrasah - sunarti, sri; Bahri, Saiful; Diana, Nirva; Etek, Yurnalis; Komariah, Aan (Inovasi: Jurnal Diklat Keagamaan, 2025)
The purpose of this study was to determine the role of teachers in the digital era, the effectiveness of Madrasah management and administration and the influence of digital transformation in improving the effectiveness of Madrasah management and administration and the influence of digital transformation in improving the effectiveness of Madrasah management and administration. This study uses a mix-method approach with meta-analysis and quantitative methods by distributing questionnaires to teachers in various Madrasahs in Lampung Province. The results of the study indicate that the role of teachers in the digital era is very important because teachers not only teach, educate, train and guide but also improve professionalism by understanding and applying technology in learning. With the role of teachers in technology, the effectiveness of Madrasah management and administration can be improved so that all learning planning and administrative governance become neater and better. From the questionnaire results, around 65% of teachers stated that there was a good improvement in managing learning, administration, teacher and parent interactions, reducing workload, supporting changes in teacher roles, supporting digital technology updates, and making Madrasah management and administration effectively.